THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING STRATEGY ON STUDENTS' CRITICAL THINKING SKILLS - Ansori, Ansori (International Conference on Humanity Education and Society (ICHES), 2025)
The aim of this research is to find out how high school students' critical thinking abilities are affected when using the Contextual Teaching and Learning (CTL) methodology. The question asked is whether, compared with traditional learning and limited learning based on Contextual Teaching and Learning (CTL), students' critical thinking abilities can be significantly improved with CTL-based learning. This study uses a quantitative experimental method with a pretest-posttest research design, which involves three groups: one experimental group using Contextual Teaching and Learning (CTL), and two control groups using conventional learning and Contextual Teaching and Learning-based learning (CTL) limited. The research sample consisted of three classes selected by purposive sampling at Tamanan Bondowoso State High School. Data was collected using pretest and posttest to measure students' critical thinking skills, as well as questionnaires to explore related aspects. The data analysis technique used is a simple linear regression analysis with the help of SPSS software. The findings demonstrate that students' critical thinking abilities significantly improve when Contextual Teaching and Learning (CTL) is used. The Contextual Teaching and Learning (CTL) experimental group outperformed both the positive control group (58.65) and the negative control group (64.29), with an average posttest score of 74.12. With a regression coefficient of 0.467 and a significance value of 0.000 (p < 0.05), the findings of a straightforward linear regression analysis demonstrated that Contextual Teaching and Learning (CTL) significantly improved students' critical thinking abilities. These results demonstrate the effectiveness of the Contextual Teaching and Learning (CTL) approach in raising high school students' critical thinking abilities.